New VMD2 gene mutations identified in patients affected by Best vitelliform macular dystrophy. Issue 3 (7th February 2007) - Marchant, D; Yu, K; Bigot, K; Roche, O; Germain, A; Bonneau, D; Drouin-Garraud, V; Schorderet, D F; Munier, F; Schmidt, D; Le Neindre, P; Marsac, C; et al.
Abstract : Purpose: The mutations responsible for Best vitelliform macular dystrophy (BVMD) are found in a gene called VMD2 . The VMD2 gene encodes a transmembrane protein named bestrophin-1 (hBest1) which is a Ca 2+ -sensitive chloride channel. This study was performed to identify disease-specific mutations in 27 patients with BVMD. Because this disease is characterised by an alteration in Cl − channel function, patch clamp analysis was used to test the hypothesis that one of the VMD2 mutated variants causes the disease. Methods: Direct sequencing analysis of the 11 VMD2 exons was performed to detect new abnormal sequences. The mutant of hBest1 was expressed in HEK-293 cells and the associated Cl − current was examined using whole-cell patch clamp analysis. Results: Six new VMD2 mutations were identified, located exclusively in exons four, six and eight. One of these mutations (Q293H) was particularly severe. Patch clamp analysis of human embryonic kidney cells expressing the Q293H mutant showed that this mutant channel is non-functional. Furthermore, the Q293H mutant inhibited the function of wild-type bestrophin-1 channels in a dominant negative manner. Conclusions: This study provides further support for the idea that mutations in VMD2 are a necessary factor for Best disease. However, because variable expressivity of VMD2 was observed in a family with the Q293H mutation, it is also clear that a disease-linked mutation in VMD2 is not sufficient to produce BVMD. The finding that the Q293H mutant does not form functional channels in the membrane could be explained either by disruption of channel conductance or gating mechanisms or by improper trafficking of the protein to the plasma membrane.